Apropriação de novas significações das operações fundamentais de matemática por professores em atividade de formação de modo remoto - Pereira, Mariana Martins (2022)
This research aimed to investigate, analyze and understand the formative movement of teachers who teach mathematics in the early years, as they establish new meanings for the four fundamental operations. The thesis defended in this work is that the intentional organization of a learning space based on the cultural-historical perspective, with AOF as its theoretical and methodological basis, can put the teacher into activity, and the only understandable motives can become effective motives. This occurs when teachers, by the inter-relation with their peers and/or teacher researchers, attribute new meanings to their pedagogical activity, by appropriating ways to organize teaching for the formation of theoretical thinking and scientific concepts in students. The object of the investigation was the appropriation of new meanings for the fundamental operations by teachers, in a learning space organized as an extension course, in a virtual environment, with the participation of 34 students qualified to teach in the early years of elementary school. From these 34 students, 12 female teachers were selected as representatives of certain time intervals of teaching performance. The production of empirical material for analysis resulted from the resources available in Moodle and also from the recordings of online classes (reflective sessions), via WebConference Platform, the MConf. For analysis, this material was organized in two isolates: formative needs and appropriation of new meanings. The results highlight that when teachers have the opportunity to participate in a learning space in which the negotiation of meanings about the fundamental operations are made possible, there may be changes in their personal meanings, which are expressed in the social meaning of this concept. This process of appropriation of new meanings of the fundamental operations by teachers can occur through the appropriation of mental actions about what it means to add, subtract, multiply, and divide. Through the analyses performed, it is highlighted that the remote mode, as one of the mediation instruments, can enable teachers to become active, transforming meanings, in a process of consciousness-raising. For this, some essential actions were listed in the organization of this space: Theoretical foundation from the THC; intentionality in the organization of the training actions; constitution of a training group with, in its majority, teachers with a degree in Mathematics; collective meetings for study and planning among the teacher trainers; participation of teachers from other universities and scholars of the research theme; and, finally, the technical support of the #UFUEmCasa program in partnership with the Center for Distance Education (CEaD) and the Dean of Extension and Culture (Proexc) of the Federal University of Uberlândia (UFU). In this sense, it is emphasized that the organization of teaching needs to be intentional and that the mastery of theoretical and methodological tools by the teacher is necessary, because only then will it be possible to provide in the school environment a teaching that promotes student learning and, consequently, their psychic development.